Timing and Intensity of Weather Events Shape Nestling Development Strategies in Three Alpine Breeding Songbirds - de Zwaan, Devin R.; Drake, Anna; Greenwood, Jennifer L.; Martin, Kathy (Frontiers in Ecology and Evolution, 2020)
Across taxa, offspring size traits are linked to survival and life-time fitness. Inclement weather can be a major constraint on offspring growth and parental care. Despite the adaptive benefits of larger offspring, we have a limited understanding of the effects of severe environmental conditions across developmental stages and how coping strategies differ among species. We assessed the influence of inclement weather on offspring size and mass traits within populations of three alpine breeding songbirds in British Columbia: 1) horned lark (Eremophila alpestris), 2) dark-eyed junco (Junco hyemalis), and 3) savannah sparrow (Passerculus sandwichensis). Specifically, we investigated at which stages during early-life development offspring are most vulnerable to inclement weather and whether thresholds exist in the developmental response to severe weather events. Across species, we identified two critical periods that best predicted offspring size: 1) clutch initiation, and 2) the nestling stage. Colder temperatures experienced by the female during clutch initiation were associated with larger, heavier offspring in horned larks but smaller offspring for savannah sparrows, indicating the potential for maternal effects, albeit acting through different mechanisms. Additionally, horned lark offspring were resilient to colder average temperatures during the nestling stage but were vulnerable to extreme cold events and multi-day storms. In contrast, dark-eyed junco nestlings were robust to storms, but smaller size and mass traits were associated with lower daily maximum temperatures (i.e., more mild temperature challenges). We suggest species differences may be linked to life-history traits, such as: 1) the thermoregulatory benefits of larger body mass in horned larks, 2) the benefits of greater nest cover to buffer dark-eyed junco against precipitation events, and 3) delayed clutch initiation for savannah sparrows to limit exposure to cold storms. We provide evidence for stage-specific impacts of inclement weather on offspring development with implications for reproductive success. These results advance our understanding of early-life resilience to stochastic environments, as we may be able to predict differences in the vulnerability of alpine species to increasingly variable and severe weather conditions.